Pengaruh Tingkat Ketuaan Daun Terhadap Karakteristik Teh Herbal Daun Sirsak (Annona muricata Linn.) - Agus S. Diputra, Pande Made; Yusasrini, Ni Luh Ari; Mayun Permana, I Dewa Gde (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p03, 2023)
The purpose of this study was to determine the effect of different levels of leaf aging on the characteristics of soursop leaf herbal tea and to determine the level of soursop leaf aging which can produce soursop herbal tea with the best characteristics. This study used a completely randomized design (CRD) with 3 levels of leaf aging treatment, namely young leaves, half old leaves and old leaves. Parameters observed in this study included water content, ash content, crude fiber content, extract content in water, total phenol, total flavonoid, tannin content, antioxidant activity, and sensory assessment which included color, aroma, taste, and overall acceptance ( hedonic test) soursop herbal tea and color and taste (scoring test) soursop herbal tea. The results showed that the difference in the level of leaf aging had a very significant effect on water content, ash content, crude fiber content, extract content in water, total phenol, total flavonoid, tannin content, antioxidant activity, and sensory characteristics including color and aroma. Soursop herbal tea prepared from young leaves had the best characteristics with criteria of water content 7.69%, ash content 5.86%, crude fiber content 17.62%, extract in water 121.25%, total phenol 2.76%, total flavonoids 2.66%, tannin content 3.26%, antioxidant activity 55.87%, the hedonic sensory characteristics of color, aroma, taste, and overall acceptability were neutral, and the scoring sensory characteristics of color was reddish yellow and taste was a little bitter.